Evaluation of intratubular penetration of Bio-C Sealer: a calcium silicate-based sealer - Pelisser, Edson (2022)
This study aimed to evaluate the intratubular penetration of Bio-C Sealer using confocal laser scanning microscopy (CLSM). Sixty canines were divided into four groups (n = 15): Bio-C Sealer, Endo Sequence BC Sealer, Sealer Plus BC, and AH Plus. Three 1-mm thick discs were obtained from each sample and analyzed to determine the area and maximum penetration depth of the sealers. Bio-C Sealer showed maximum penetration in the cervical and middle third, lower than the AH Plus (p < 0.05) but similar to the other calcium silicate sealers evaluated (p > 0.05). In the apical thirds, there was no difference between the sealers (p > 0.05). The area of penetration of Bio-C Sealer was similar to AH Plus and calcium silicate sealers (p > 0.05). Hence, it can be concluded that Bio-C Sealer had similar intratubular penetration as the other tested sealers, and it can be used as an endodontic sealer.